Analysis Factors that Influence the Role of West Kalimantan Legislative in Budget Monitoring - DESTY, CHRYSTINA ELVINDO DESTY B1034131016 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACTThis study is quantitative method by using primary data that is collected by using the questionnaire. The questionnaire is distributed to legislative member. The population and sample of this research is West Kalimantan legislative member 2014 – 2019 period. The analysis for the data result in this research is using quality data test ( validity test and reliability test), descriptive statistic test, classic assumption test (normality test, multicollinearity test, and heterokedasticity test), and double regression analysis (statistic t test and coefficient determination ( R square)). Where in this research consist of some hypothesis that will be examine by using the that test are 1) the training and education has significant influence to the role of legislative member in budget monitoring. 2) the experience in organization has significant influence to the role of legislative member in budget monitoring. 3) the knowledge about budgeting has significant influence to the role of legislative member in budget monitoring. Based on that hyphothesis the result of this research as follow: 1) Training and education has positive influence but not significant to the role of legislative in budget monitoring. 2) Experience in organization has positive influence but not significant to the role of legislative in budget monitoring. 3) Knowledge about budgeting has positive influence and significant to the role of legislative in budget monitoring. Keywords : training and education, experience in organization, knowledge about budgeting and role of legislative in budget monitoring